Expression and Biological Evaluation of an Engineered Recombinant L-asparaginase Designed by In Silico Method Based on Sequence of the Enzyme from Escherichia coli - Mahrokh Dastmalchi; Mahdiyeh Alizadeh; Omid Jamshidi-Kandjan; Hassan Rezazadeh; Maryam Hamzeh-Mivehroud; Mohammad M Farajollahi; Siavoush Dastmalchi (Tabriz University of Medical Sciences, 2023)
Purpose: Medical usage of L-asparaginase (ASNase), the first-line of acute lymphoblastic leukemia treatment, is linked to allergic responses and toxicities, which necessitates the development of new bio-better ASNases. The aim of the current study was in silico design of a novel ASNase with predicted improved enzymatic properties using strategies encompassing sequence-function analysis of known ASNase mutants. Additionally, current study aimed to show that the new enzyme is active. Methods: Based on 21 experimentally reported mutations for ASNase, a virtual library of mutated enzymes with all 7546 possible combinations of up to 4 mutations was generated. Three-dimensional models of proposed mutant enzymes were built and their in silico stabilities were calculated. The most promising mutant was selected for preparing a genetic construct suitable for expression of the designed ASNase in bacterial cells. Results: Computational study predicted that Y176F/S241C double mutation of Escherichia coli ASNase may increase its folding stability. The designed ASNase was expressed in two different E. coli strains (Origami B(DE3) and BL21(DE3)pLysS) and then the soluble fractions prepared from the cell lysates of the host cells were used in enzyme activity assay. Results showed that enzyme activity of soluble fraction from Origami (95.4±7.5 IU/0.1 mL) was four times higher than that of soluble fraction from pLysS (25.8±2.5 IU/0.1 mL). Conclusion: A novel functional double mutant ASNase with predicted improved enzymatic properties was designed and produced in E. coli. The results of the current study suggest a great commercial potential for the identified enzyme in pharmaceutical and industrial applications.